The Effect of Interest Rates on Portfolio Investments and Foreign Direct Investments in Türkiye - Selcuk Kendirli; Levent Sezal (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This study aims to analyse the relationship between foreign direct investments (FDI) and portfolio investments (PI) and interest rates. Firstly, ADF and PP unit root tests were applied to determine whether the variables were stationary or not. Since the series became stationary at different levels, the ARDL (Autoregressive Distributed Lag Bound Test) test, one of the cointegration tests, was applied. Afterward, Toda-Yamamoto tests were utilized to determine whether there is causality between the variables and if there is a causality relationship, to determine its directions. According to the ARDL bound test results, it is concluded that there is no short-term asymmetric relationship between PI and other independent variables. In other words, there is no statistically significant relationship between PI and EUR, USD and TL interest rates. On the other hand, it is concluded that the FDI dependent variable and other independent variables are long-run cointegrated in the relevant period. According to the results of the Toda-Yamamoto causality test where FDI and TL, EUR, and USD are independent variables, it is concluded that there is a Granger causality relationship between FDI and TL and EUR interest rates.